PUBLIC SERVICE COLLABORATION ON RESPECT, PROTECTION AND FULFILLMENT OF THE RIGHTS OF PERSONS WITH DISABILITIES IN SUKABUMI CITY IN 2023 - Rahmadhani, Rayhan; Fajar FY. Basori, Yana; Purwanti, Dian (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Human rights are universal rights that must be protected, including the rights of people with disabilities. This study aims to explore collaboration in public services for people with disabilities in Sukabumi City, through collaboration between the Social Service and PD Nasyiatul 'Aisyiyah. The research method used is qualitative, with interviews and analysis of collaboration theory. The results of the study indicate that although collaboration has been established, there are challenges such as the lack of formal structures (MoU) and suboptimal community participation. This study concludes that improving formal structures and participation can improve the inclusiveness of public services for people with disabilities. Thus, this collaboration has the potential to become a best practice model in inclusive public services. The contribution of this study is to provide empirical insight into the practice of collaboration in inclusive public services, especially for people with disabilities, at the local level. Identifying inhibiting and supporting factors in cross-sector collaboration that can be used as a reference for similar policies and practices in other areas. Offering recommendations for strengthening formal structures and increasing community participation as strategic steps towards more inclusive public services. And providing an initial framework that can be adapted as a best practice model in public service collaboration to improve the welfare of people with disabilities.